The health, wellbeing and quality of life of Iranian transgender people - Haddadpour, Abbas (Curtin University, 2024)
This study explores the lived experiences of transgender individuals in Iran, focusing on health, wellbeing, and quality of life. Utilizing mixed methods, it reveals significant mental health challenges and quality of life disparities faced by this community. Key themes include societal treatment, healthcare access, and the impact of discrimination. The findings highlight urgent needs for improved support and awareness to enhance the health and wellbeing of transgender people in Iran.